A Review of Regenerative Braking Methods for Induction Motors in Electric Propulsion System - Nur Sabilillah, Muhammad Rifqi; Rini Nur Hasanah; Muslim, Muhammad Aziz; Sulistiyanto, Nanang (Faculty of Engineering, Universitas Brawijaya, 2024)
This paper provides a comprehensive review of regenerative braking methods for induction motors utilized in electric propulsion systems. Regenerative braking is a crucial technology for enhancing the energy efficiency of electric vehicles (EVs) and hybrid electric vehicles (HEVs) by converting kinetic energy back into electrical energy during braking. The review focuses on several regenerative braking techniques, including self-excited regenerative braking using capacitors and inverter-based regenerative braking. By evaluating the efficiency, cost-effectiveness, and practical applications of these methods, the paper identifies the strengths and weaknesses of each approach. Additionally, recent advancements in the field are discussed, along with suggestions for future research directions to optimize energy recovery in electric propulsion systems. The goal is to provide valuable insights for engineers and researchers working towards the development of more efficient and cost-effective regenerative braking systems, ultimately contributing to the advancement of electric and hybrid vehicle technologies.